Market attractiveness, resource-based capabilities, venture strategies, and venture performance - Chandler, Gaylen N.; Hanks, Steven H. (Journal of Business Venturing, 1994)
This research seeks to identify variables that should be related to venture performance. It is hypothesized that both market attractiveness and resource-based capabilities are directly related to new venture performance. In addition, specific resource-based capabilities are hypothesized to be directly related to the competitive strategies chosen by a firm. Finally, the “fit” between strategies and resource-based capabilities is hypothesized to be related to venture performance. The sample consisted of all manufacturing businesses (SIC codes 20–39) started or reorganized in the corporate form between 1980 and 1991 in nine counties in northwestern Pennsylvania, as identified by a major marketing research service. Of the 800 companies surveyed, completed questionnaires were returned for 155, representing a 19% response rate. The 155 responding companies had a median age of 5 years with a median of 15 employees. The major products of companies in the sample included flour, lumber, household and office furniture, plastic containers, tools and dies, ready mixed concrete, pipe fittings, measuring devices, paint and varnish, machine tools, electroplate, carbon and graphite composite products, plastic laminated products, circuit boards, electronic components, and parts for internal combustion engines. In general, the results confirm the validity of the measures of environmental and organizational characteristics as we have adapted them for new ventures. As hypothesized, perceived market attractiveness and the overall abundance of resource-based capabilities were significantly related to venture performance. Also, in two of three cases, the evidence suggests that specific resource-based capabilities are related to the firm's stated competitive strategies. Finally, although the relationship between “fit” and performance is not supported in all cases, the performance of the emerging manufacturing ventures included in this sample appears to be enhanced when resource-based capabilities are supportive of a cost leadership strategy and when firms seeking to differentiate based on product and service quality have the resource-based capabilities to support that strategy. The results of this emerging research stream will make an important contribution to our understanding of the factors that impact firm performance. For scholars the results provide additional information needed to develop comprehensive new venture performance models. A clear understanding of the factors that have a strong influence on venture performance will enable practitioners to better identify viable business opportunities and academicians to provide potential business founders with tools to help them recognize opportunity. In addition, the identification of appropriate levels of abstraction will provide building blocks for future research that seeks to integrate environmental and firm-level constructs.